Formulation and Antioxidant Evaluation of Clay Masks Containing Robusta Coffee Pulp Extract - Fith Khaira Nursal; Anisa Amalia; Karsiti Karsiti; Sri Nevi Gantini (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
The pulp of robusta coffee (Coffea canephora L.) is known to contain chlorogenic acid compounds that have potential as antioxidants. The content of this compound can be utilized as an active ingredient in cosmetics such as clay masks. The main component that affects the physical properties of a clay mask is the clay base. This study aims to develop a clay mask formulation from robusta coffee pulp extract with variations in the concentration of base combinations, namely bentonite and kaolin, and to observe their effects on the physical properties of the dosage form. The base concentration variations used were 20% (F1), 25% (F2), and 30% (F3) with a bentonite to kaolin ratio of 1:2. The evaluation of physical properties included organoleptic tests, homogeneity tests, pH tests, spreadability tests, adhesion tests, viscosity tests, and drying time measurements. The evaluation results showed that all clay masks were homogeneous with pH values ranging from 5.15 ± 0.04 to 5.29 ± 0.12, spreadability values of 4.60 ± 0.22 to 4.74 ± 0.37 cm, adhesion values of 0.82 ± 0.11 to 1.16 ± 0.15 seconds, and viscosity ranged from 5501 ± 670.22 to 7567.67 ± 220.30 mPa.s, and drying time ranged from 20.60 ± 0.39 to 25.34 ± 0.80 minutes. Results of the antioxidant activity test indicated that the clay mask made from robusta coffee pulp extract is a powerful antioxidant with IC50 values of 28.31 ± 4.72 to 30.45 ± 5.69 ppm. Variations in the concentration of the clay mask base significantly (p < 0.05) affected the viscosity and drying time of the dosage form. In summary, the clay mask formulations satisfied the essential physical criteria and showed promise for cosmetic application. F3 emerged as the leading formula, exhibiting the highest antioxidant capacity, evidenced by its lowest IC₅₀ value.